(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2020)
A lack of policy and regulatory frameworks to administer and recognize marriage institutions especially among Rohingya refugees in Malaysia gives rise to various legal and social implications, non-compliance with Sharia law, as well as complications in the process of refugee resettlement to third countries. This research aims to discuss this issue including its repercussions from the legal and Sharia perspectives in Malaysia. It employs a qualitative methodology using library research and semi-structured interviews based on the purposive sampling technique with a number of respondents from the Islamic Religious Departments of Selangor, Federal Territory of Kuala Lumpur and Negeri Sembilan. These three states were selected taking into consideration their socio-economic conditions and employment opportunities, which serve as attractive destinations for migrants and refugees from various countries. This study reveals that the unrecognized legal status of refugees complicates the registration of Rohingya marriages in this country. Additionally, state autonomy in setting out the policies, laws and guidelines on the registration of marriages and divorces of Muslim refugees in Malaysia creates divergence in the management of their marriages. A streamlined and detailed set of guidelines should be finalized between the states and the relevant federal agencies so that marriages among Muslim refugees, including the Rohingya, can be better regulated, culminating in preservation of their rights and of Islamic law. Keywords: Birth registration, Islamic Religious Department, legal identity, marriage, refugees, Rohingya, UNHCR